Aspergillus terreus Endogenous Endophthalmitis in a Nonimmunocompromised Patient with a History of Bronchiectasis. (June 2013) - Ng, James; Ho, Su; Krishnan, Prabha; Teoh, Stephen C.
Abstract To present the first case of Aspergillus terreus endophthalmitis in a patient without previous ocular surgery or immunocompromised status with a review of literature.